Abstract Number ‐ 7: Final Angiographic, Clinical and Thrombus Composition Results of 1000 Patients in the EXCELLENT Registry - Nogueira, Raul G; Andersson, Tommy; Yoo, Albert J; Hanel, Ricardo A; Zaidat, Osama O; Hacke, Werner; Jovin, Tudor; Fiehler, Jens; De Meyer, Simon F; Brinjikji, Waleed; Doyle, Karen; Liebeskind, David S; et al. (STROKE: VASCULAR AND INTERVENTIONAL NEUROLOGY, 2023)
IntroductionEXCELLENT (NCT03685578; Cerenovus) is a large, prospective, international, real‐world registry of endovascular clot removal in acute ischemic stroke (AIS) with EmboTrap as the first line mechanical thrombectomy (MT) device, which included collection and analysis of the retrieved thrombus material.MethodsBetween September 2018 and March 2021, 1000 “all‐comer” patients were enrolled at 34 global sites (27 US, 5 EU, 1 UK, 1 Israel) and treated according to standard of care at each center (with Embrotrap as first line). The study employed blind endpoint evaluation, including a core imaging lab and an independent 90‐day mRS assessment. Retrieved clot was collected per each MT maneuver from 538 subjects across 26 sites and clot analysis was performed by independent central labs blinded to clinical data.ResultsmITT population included 998 subjects. Mean age was 69.9±14.18 years (range 18–102), 51.8% (517/998) subjects were female and 9.9% (97/997) had a pre‐stroke mRS 3–5. Baseline NIHSS was 15.6±6.87 (range 0–36); 10.1% (82/815) subjects had a large core (ASPECTS 0–5); 5.8% (57/990) had posterior stroke; 56.3% (523/929) underwent MT ≤ 6hrs of onset and 38.1% (380/998) received IV‐tPA prior to MT. First pass eTICI 2c‐3 was achieved in 38.3% (377/984) and final 2b‐3 in 94.5 % (930/984; median number of passes = 1) of subjects. 90‐day mRS≤2 or ≤pre‐stroke was 46.9% (429/915) and 90‐day all‐cause mortality was 19.0% (175/921). The univariate analysis of clot components showed high red blood cell and low platelet content were significant predictors of good mRS outcome (p < 0.001 and 0.009) and negative predictors of 90‐day mortality (p < 0.001 and 0.017, respectively).ConclusionsThis large multi‐center, all‐comer cohort reflects the population undergoing thrombectomy today in a real world‐setting. Final angiographic, clinical and thrombus composition results, along with multivariate analysis of predictors of clinical outcomes, will be presented at the time of the conference.